ANALISIS KESALAHAN SISWA DAN SCAFFOLDING DALAM MENYELESAIKAN SOAL PADA MATERI PERSAMAAN KUADRAT - Cindy Indra Amirul Fiqri; Gatot Muhsetyo; Abdul Qohar (Jurnal Kajian Pembelajaran Matematika, 2019)
to identity the types of errors made by students to solving the problem of quadratic equations in SMK Kartika IV-1 Malang. Research method used is qualitative descriptive research. Subject in the research were 3 students with low, medium, high mathematics ability category. Based on the analysis of obtained can be concluded that studen make conceptual errors, procedural errors, and computation errors. For example factor causing the students to make errors are the students less mastered and understand the matter about quadratic equations, students are less thorough the problem and student not understand step by step to solving problem of quaratic equations.